ANALISIS PASAR OBLIGASI PEMERINTAH DI INDONESIA - Hastin, Mira; Idris, Idris; Aimon, Hasdi (Jurnal Kajian Ekonomi, 2013)
ABSTRACT This article focused on analyze (1) Effect of the budget deficit, official foreign borrowing, certificate of Bank Indonesia (SBI), and demand of the government bonds to the issuances of the government bonds in Indonesia. (2) The influence certificate of Bank Indonesia (SBI), bond price, (Composite Stock Price Index) IHSG, and supply of the government bonds to demand of the government bonds in Indonesia. Data used time series of (I year kuartal 2004 – IV year kuartal 2011). This article use analyzer model equation of simultaneous with method of Two Stage Least Squared (TSLS). The result of research concludes that (1) the budget deficit have a significant and positive impact on supply of the government bonds, official foreign borrowing, certificate of Bank Indonesia (SBI) and demand of the government bonds significantly and negatively influence on issuances of government bonds. (2) The influence certificate of Bank Indonesia (SBI) have a significant and positive impact on demand of government bonds, IHSG  and supply of the government bonds significantly and negatively on demand of  government bonds in Indonesia. While the bond price is not significant and negative effect  on demand of the government bonds in Indonesia. Keywords : budget deficit, official foreign borrowing, certificate of Bank Indonesia (SBI), bond price, (Composite Stock Price Index) IHSG, demand of the government bonds, and spply of the government bonds